Continuous production of CuO nanoparticles in a rotating packed bed. Issue 2 (1st February 2016) - Lin, Chia-Chang; Wu, Min-Shan
Abstract: Copper oxide (CuO) nanoparticles can be prepared by the precipitation method in a rotating packed bed (RPB). The precursors of CuO nanoparticles were firstly prepared in continuous mode by a liquid–liquid reaction of copper sulfate (CuSO4 ) and sodium carbonate (Na2 CO3 ). A CuSO4 concentration of 0.4 mol/L, an Na2 CO3 concentration of 0.4 mol/L, a rotational speed of 600 rpm, and a flow rate of 0.5 L/min were used. Then, the precursors were calcined at 500 °C for 1 h to yield CuO nanoparticles with a crystallite size of 20.1 nm, as determined by XRD, and an average size of 27.5 nm, as estimated by TEM. The rate of production of CuO nanoparticles was 19.9 kg/day. Accordingly, the precipitation method in an RPB has potential for the mass-production of CuO nanoparticles.